Jejak Virtual: Peran Media Sosial Dalam Mengangkat Kasus Kopi Sianida Melalui Film Dokumenter 'Ice Cold' - Yosia Geral Lyshady; Binsar Steven Immanuel Pasaribu; Gabriel Riung Mahda (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
The cyanide coffee murder case involving Jessica Wongso as a suspect in the murder of the victim Wayan Mirna Salihin had become a hot topic in the mass media. In 2017, the case was finalized with the decision of the Supreme Court which declared Jessica as a murder suspect with a sentence of 20 years in prison. Until the release of a documentary entitled Ice Cold Murder, Coffee, and Jessica. With the rapid development of technology, anyone who does not watch the documentary Ice Cold: Murder, Coffee, and Jessica can watch footage spread across Social Media. Public opinion began to change after the release of the documentary. The public considered that many irregularities occurred in this murder case. This research aims to review the role of social media in the dissemination of the Ice Cold documentary, so that the public can find new things that have not previously been discussed during the trial, using qualitative research methods: case studies. Social media acts as a harmonizer in which social media has the ability to unify perspectives from diverse public responses on social media networks.